Programa de integridade na Lei nº 12.846/2013 - Lima, Ana Júlia Andrade Vaz de (2018)
Law No 12.846/2013, named Anticorruption Law, states, in its content, the possibility of diminishing the penalties eventually imposed upon corruptive legal entities if identified the existence of a Compliance Program, or, as described in the law, “internal mechanisms and procedures of integrity, audit and incentives towards the denunciation of wrongdoings, as well as the effective appliance of codes of ethics and conduct”. In that regard, this paper intends to study the concept and content of the Compliance program, which authorizes the diminishment of penalties in accordance with the law. Initially, we will address the context of Law No 12.846/2013 and, furthermore, approach the main subjects presented by the law – punitive field in which it is inserted; legal entities’ strict, administrative and civil liabilities; illicit acts; penalties; administrative liability procedure; judicial liability procedure; and leniency agreement. Subsequently, we will analyze both conceptual and legal aspects of the Compliance Program, under the scope of Federal Decree No 8.420/2015, which regulates the subject. Furthermore, the structure of the Compliance Program will be introduced and analyzed in order to present, at the end of this paper, the legal consequences that the Program develops, whether concerning the penalties calculus or the execution of a leniency agreement